2019
DOI: 10.1038/s41598-019-46494-0
|View full text |Cite
|
Sign up to set email alerts
|

Molecular community profiling of the bacterial microbiota associated with denture-related stomatitis

Abstract: Denture-associated stomatitis (DS) affects over two-thirds of denture-wearers. DS presents as erythema of the palatal mucosa in areas where denture-surface associated polymicrobial biofilms containing the fungus Candida albicans exist. The contribution of the oral bacterial microbiota toward the infection is unknown. Therefore, this study characterised the bacterial microbiota of sites within the oral cavity to identify potential associations with occurrence of DS. Denture-wearing patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 42 publications
1
10
0
1
Order By: Relevance
“…In healthy patients with denture candidiasis an enrichment of the tongue mucosa with Enterococci and Streptococci was recently reported [54]. This finding supports the concept that candidiasis occurs in a polymicrobial environment enriched with these bacteria consistent with our mouse tongue infection models [13,[15][16][17]49].…”
Section: Evidence For Bacterial Dybiosis In Oropharyngeal Candidiasissupporting
confidence: 91%
“…In healthy patients with denture candidiasis an enrichment of the tongue mucosa with Enterococci and Streptococci was recently reported [54]. This finding supports the concept that candidiasis occurs in a polymicrobial environment enriched with these bacteria consistent with our mouse tongue infection models [13,[15][16][17]49].…”
Section: Evidence For Bacterial Dybiosis In Oropharyngeal Candidiasissupporting
confidence: 91%
“…A large percentage of denture wearers are affected by denture-associated stomatitis, which is mainly caused by Candida albicans [ 125 ], albeit also differences in denture-associated biofilms on the genus and species level of other microorganisms can be detected between patients affected by denture-associated stomatitis and healthy subjects [ 126 ]. Dentures are mostly manufactured from polymethylmethacrylate (PMMA).…”
Section: Bioadhesion In the Oral Cavitymentioning
confidence: 99%
“…Our research group has previously shown that DC treatment in vitro can alleviate C. albicans biofilm growth on denture material [ 22 ]. The presence of a complex polymicrobial biofilm on the denture surface is also an important factor in disease pathogenesis [ 6 , 12 ]. Candida is essential for supporting the growth of bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, there is evidence that interkingdom interactions play a critical role in protecting fungal and bacterial species from antibiotics and antifungals [ 9 , 10 ]. Recent research has highlighted the complexity of the biofilms present on the surface of dentures [ 6 , 11 , 12 , 13 ]. Thus, in vitro biofilm models investigating DS need to reflect the interkingdom dynamic for accurate and representative antimicrobial testing of oral healthcare products, such as denture cleansers and toothpastes.…”
Section: Introductionmentioning
confidence: 99%